Convergent validity of the engagement in meaningful activities survey in a college sample - Eakman, Aaron M., author; American Occupational Therapy Foundation, publisher (Colorado State University. Libraries, 2011)
The Engagement in Meaningful Activities Survey (EMAS) (Goldberg, Brintnell, & Goldberg, 2002) demonstrated sufficient psychometric properties in a sample of 122 adults. The EMAS was found to have adequate test-retest (r = .71) and internal consistency (α = .88) reliability; significant positive correlations between the EMAS and the subscales of the Basic Psychological Needs Scale and the Sources of Meaning Profile and negative zero-order correlations were found with short form versions of the Boredom Proneness Scale and the Depression, Anxiety, and Stress Scales. Step-wise multiple regression analysis results showed the Sources of Meaning Profile, Boredom Proneness Scale, and Competence subscale of the Basic Psychological Needs scale best predicted the EMAS. These results lend additional construct validity evidence in support of the EMAS as a brief measure of meaningful activity participation.
Final, peer-reviewed manuscript.
Keywords: psychometrics; self determination; boredom; depression; human activities